KAJIAN MODEL BISNIS UNTUK PENGELOLAAN KAWASAN STASIUN MRT JAKARTA BESERTA ATURAN HUKUM PEMANFAATAN RUANG YANG DIPERLUKAN - Indra Gunawan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
DKI Jakarta is a center of economic activity and according to Perda 1/2014, RDTR and PZ, the construction of railway infrastructure (MRT) base on TOD that optimized the utilization of Underground Space (RBT) is a must to improve public facilities and urban transportation. However, the implementation of the construction requires land that could be an obstacle in land acquisition process and the relatively high cost of JICA Loans (Foreign loans). Business Management in the TOD area of the MRT Station by PT MRT Jakarta (Perseroda) requires the right business model to increase potential revenue that provides additional income for PT MRT Jakarta to reduce government subsidies, Improvement of public facilities around the station which is expected to generate new business generation. This study uses a descriptive qualitative method by interviewing informants from representatives of landowners, DKI Jakarta provincial government staff (Dishub) and PT MRT Jakarta employees to get an overview related to the sustainable business model for the management of the Jakarta MRT station area along with the legal rules for the use of space required with business model references are Rail plus Property (R+P) with TOD and LVC approach which is applied in countries that already have good MRT system such as MTRc Hong Kong, Shenzhen, WMATA in DC Maryland Virginia – DMV. Based on the results of interviews and literature studies, it was found that the R+P business model in the TOD area of the Jakarta MRT station is the right business model if MRT Jakarta gets land use rights around the MRT station from the Government and revision of the UUPA that is in line with the use of RBT so that it can increase potential revenue, business diversification and improvement of public facilities that lead business generation in the transit area.